Prioritization Of Zakat Distribution In Malaysia - Kader Mydin, Muhammad Kamil (2020)
Efficient and effective collection and distribution of zakat fund are one of the keys successful mission of Zakat operator. Many past studies have been focused on the role of Zakat in the society especially on the poverty alleviation. The aims of the present study are to examine the priority of zakat recipients to receive zakat from the year 2007 to the year 2015. The present study employed secondary data of distribution of zakat funds according to zakat recipients from the year 2007 to the year 2015 of each state in Malaysia except for Perlis, and the data are obtained from Jabatan Wakaf, Zakat dan Haji (JAWHAR) and zakat institutions websites. First objective is to identify the rank of the recipients, present study employed the Analytical Hierarchy Process (AHP) technique which compared zakat recipients for each state in Malaysia using pair-wise technique analysis.